PERFORMANCES ORDERING IN LONG – DISTANCE PASSENGER RAIL TRANSPORT IN THE SLOVAK REPUBLIC (Perner's Contacts, 2017)
The reforms in the railway transport and the gradual opening up of the rail sector started EU already in the 90s of the 20th century application of the relevant directives and regulatory measures. A fundamental step in the liberalization of rail transport was unbundling of infrastructure from rail transport undertakings and subsequently provide non-discriminatory access to new carrier to the infrastructure in all Member States. The paper is focused on the analysis of the successive steps of the Slovak Government in the promulgation of the first tender for the provision of transport services which are subsidized, and also set the conditions for this competition on a defined line.
Keywords: public performance; public tender; liberalisation of passenger transport